ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Prabowo, Menang; Lindrawati, Lindrawati; Tedjasuksmana, Budianto (Widya Mandala Surabaya Catholic University, 2014)
Value of the company is a company that conducted an ssessment of the investor in the form of perception. Value of the com-pany can be achieved by several factors, including the implementation of the financial management function, while the financial decisions take will affect the value of the company and financial management regarding the settlement of the important decisions taken by the company, including investment decisions, financing decisions, dividend policy. In addition the value of the company can also be affected by the ownership structure that includes managerial ownership and institutional ownership. institutional ownership. Therefore, this study aimed to test and analyze the effect of investment decisions, financing decisions, dividend policy, and ownership structure on firm value. The research design was quantitative with the hypothesis. Types of quantitative and qualitative data in the form of financial statements of sites Indonesia Stock Exchange and Indonesian Capital Market Directory form secondary data. The object of research is a manufacturing company that is listed on the Indonesia Stock Exchange from 2010-2012. Analysis using multiple linear regres-sion. The results showed that investment decisions, managerial ownership and institutional ownership has no effect on firm value, while the dividend policy and financing decisions have a significant positive on firm value. This suggests that the higher the divi-dend policy will provide for the welfare of shareholders and will increase the value of the company.